Donatas Sauka’s Project of Comparative Literature: “Programme Maximum“ - Speičytė, Brigita (Literatūra, 2020)
The article discusses Donatas Sauka’s study An Epilogue of Faust’s Age (1998) in order to assess the reference to “comparative literature science” expressed in the introduction to the study. The psychological and subjective motivation of comparative research arising from the context of the genesis of the work is interpreted: an aim to overcome the cultural isolation of Soviet-era humanitarian and to go beyond the methodologically narrow and largely directive Soviet-era comparative studies. It is argued that An Epilogue of Faust’s Age is a synthetic study in the field of comparative studies and world literature research, the conceptual unity of which is ensured by the attention to the category of the author in modern European literature and the state of modern consciousness revealed therein. Thus, D. Sauka in his study turns from literary comparative studies to the field of cultural studies and the history of ideas by forming a certain classical person of universal culture in the Lithuanian cultural and academic environment.